Colonic mucosal biopsy location can not affect the results of mucosal metabolomics and mucosal microbiota analysis in IBS - Zhu, Huiting; Zhang, Yanli; Du, Shiyu; Wang, Huifen; Zheng, Yue (Frontiers in Medicine, 2023)
Objective: To compare and analyze the mucosal metabolites and mucosal microbiota of different parts of colon in patients with IBS. Methods: A total of 10 patients with IBS-D and six healthy controls (HC) were enrolled. All enrolled patients underwent two biopsies of the ileocecal and sigmoid colon during colonoscopy. Metabolomic profiling of one piece of tissue was conducted using desorption electrospray ionization-mass spectrometry（DESI-MSI），and the gut flora of the other piece was examined using 16S rRNA sequencing. The metabolic profiles and flora of the ileocecal and sigmoid colonic mucosa in each group were further analyzed in this study. Results: 1. Principal components analysis (PCA) indicated that mucosal metabolites did not differ in different parts of the colon in either the IBS-D or HC groups. 2. In the mucosal microbiome analyses, no differences between the microbiota of the two parts of the colon were found by using PCA. In IBS group, comparing with sigmoid mucosa, the chao1 richness indice was lower and the Shannon index was higher in the ileocecal mucosa than in the sigmoid mucosa(P=0.40, P=0.23). However, in the HC group, microbiome analysis of the ileocecal mucosa showed higher values for Chao 1 and Shannon indices than those of the sigmoid colon mucosa (P=0.07, P=0.86). 3. Compared with the HC group, 1113 metabolic signal peaks were upregulated, whereas 594 metabolites were downregulated in the IBS-D samples. Moreover, the mucosal metabolites of the PCA showed significant separation between the IBS-D and HC groups. 4. Chao1 expression was significantly higher in the mucosal microbiota with IBS-D than in the HC (P=0.03). The Shannon index was lower in IBS-D, but the difference was not statistically significant(P=0.53). PCA revealed a significant difference in the microflora structure between the IBS-D and HS groups. Conclusion: The mucosal metabolic profile and mucosal flora structure of the colon were similar, despite different locations in IBS and healthy subjects. IBS had abnormal colonic mucosal metabolism and flora disturbances.